Participação em aulas de Educação Física, prática de atividade física e comportamento sedentário em escolares do Ensino Fundamental II: um estudo longitudinal - Silva, Diego Júnio da (2019)
Physical education (PE) classes have been considered as a space for approaching content, experiences, experiences that can lead students to develop knowledge, attitudes, positive perceptions, values and beliefs that contribute to the adoption of healthy behaviors. Bodies linked to health promotion and education have recommended that PE classes develop health promotion actions, especially with emphasis on the adoption of healthy behaviors such as physical activity and sedentary behavior reduction. However, it is not well established if schoolchildren attending physical education classes are more likely to adopt healthier behaviors. This study aimed to analyze longitudinally the association of participation in PE classes with the level of physical activity and time in sedentary behavior in elementary school students in the city of João Pessoa (PB). This is a longitudinal observational study that analyzed data from LONCAAFS (Longitudinal Study on Physical Activity, Sedentary Behavior, Eating Habits and Adolescent Health). The present study was conducted with 197 elementary school students from João Pessoa public school, who had complete data for all variables under study, from 2014 to 2017. In the present study the following variables were used: gender, age , mother's level of education and participation in PE classes, measured by questionnaire, applied in the form of face-to-face interviews; and time in moderate to vigorous physical activity (≥ 2296 counts / min) and sedentary behavior (≤ 100 counts/min), measured by Actigraph GT3x+ accelerometer. The students were instructed to use the accelerometer for seven consecutive days, removing it for water activities and sleeping. To download and reduce accelerometer data, Actlife 6.11 was used. The associations of participation in PE classes with physical activity level and time in sedentary behavior were verified by generalized estimation equations (GEE). All analyzes were performed in SPSS 15, with a significance level of 5%. Participation in two or more PE classes ranged from 95.4% (in 2014) to 86.3% (in 2017), with a declining trend (4.8% on average per year) over the years. Participation in PE classes was not associated with physical activity level (OR = 1.60; 95% CI: 1.00-2.55) and sedentary behavior (OR = 1.26; 95% CI: 0.84-1.89). Participation in PE classes was high but declined over the four years of the study and was not associated with the level of physical activity and sedentary behavior of students' extracurricular hours.